ASSESSMENT OF ROLES OF TRADITIONAL RULERS IN COMMUNITY CONFLICT MANAGEMENT IN IMO STATE - Umezulike, Nneka; Mbara, Kingsley Ugochukwu (Journal of Continuing and Development Education, 2022)
This study investigated the roles of traditional rulers in community conflict management in Imo State. The study primarily assessed the levels of use of some strategies by traditional rulers in managing conflicts in their communities. Hence the study raised 3 specific objectives which guided the study. The study adopted a descriptive survey method carried out in selected autonomous communities in Imo State. The study randomly and purposively sampled 150 traditional rulers from a population of 864. The study used a researcher made questionnaire titled “Assessment of Roles of Traditional Rulers in Community Conflict Management Questionnaire” (ARTICCMQ) to elicit relevant information from the respondents. The instrument has 27 questionnaire items and the response was patterned as thus; Very High Extent (4), High Extent (3), Low Extent (2), Very Low Extent (1) for research questions 1 and 2 and Strongly Agree (4), agree (3), disagree (2) Strongly Disagree (1) to elicit relevant information from the respondents. The instrument was validated by experts and a reliability coefficient of .86 was obtained. The questionnaire was directly administered by the researcher. The research questions were answered using mean statistics. The study revealed that traditional rulers agreed on the use of compromise and collaborating strategies in community conflict management strategies, also they agreed on the challenges encountered in the course of managing conflict in their communities. Based on the findings, the study recommended that the powers and authorities of traditional rulers should emanate from the constitution. The study also concluded that there is need for interaction with relevant stakeholders in the communities so as to reduce conflict and effectively manage conflicts in communities.